1989
DOI: 10.1212/wnl.39.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic loss in Alzheimer's disease and other dementias

Abstract: The extent and location of neuronal losses necessary or sufficient to produce dementia in patients with Alzheimer's Disease (AD) is unknown. To approach this question, we studied synaptic terminals in postmortem brain tissue utilizing immunohistochemical techniques. We used antibodies against two proteins found in synaptic terminals--synapsin I and synaptophysin--as synaptic markers in the hippocampal complexes of eight patients with autopsy-proven AD and eight nondemented control subjects. Quantitative micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
176
2
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(192 citation statements)
references
References 0 publications
13
176
2
1
Order By: Relevance
“…Its consistent low levels in Alzheimer's (which is in agreement with immunohistochemical data [19,20]) and Pick's brains can simply be an expression of neuronal and synaptic loss occurring in these diseases, but a specific loss of synaptic vesicles should also be considered. On the other hand, chromogranin A levels are increased.…”
Section: Discussionsupporting
confidence: 83%
“…Its consistent low levels in Alzheimer's (which is in agreement with immunohistochemical data [19,20]) and Pick's brains can simply be an expression of neuronal and synaptic loss occurring in these diseases, but a specific loss of synaptic vesicles should also be considered. On the other hand, chromogranin A levels are increased.…”
Section: Discussionsupporting
confidence: 83%
“…A model of KIF1B knockout mice showed reduced transport of synaptic vesicles [52]. A reduction of synaptophysin in AD brain has been reported and interpreted as evidence for synaptic loss [20,29]. We also observed this reduction of synaptophysin in the frontal cortex of AD patients.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, in vitro and also in vivo experiments have shown that soluble oligomers of A␤ are capable of inhibiting LTP (Lambert et al, 1998;Walsh et al, 2002). Together, these data demonstrate the importance of soluble forms of A␤ in mediating synaptic dysfunction and correlate with neuropathological observations in brains of patients with mild cognitive impairment and AD, where synaptic disruption and loss are early pathological features (Davies et al, 1987;Hamos et al, 1989;Masliah et al, 1991). However, there is presently little information on how A␤ may influence normal synaptic transmission in the brain, particularly in structures such as the cholinergic basal forebrain that are at the epicenter of the chemical pathology seen in AD.…”
Section: Introductionmentioning
confidence: 76%